Implementasi HRIS sebagai Sistem Pendukung Pengelolaan SDM di PT X - Aris Giovany; Nuzsep Almigo (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2026)
The use of Human Resource Information System (HRIS) is a strategic step in improving the effectiveness of human resource management in organizations. In many companies, especially those that are still transitioning from manual to digital systems, HR administration processes are often inefficient, prone to data errors, and lack integration across work units. This community service activity was carried out at Company X for approximately three months with the aim of supporting the optimization of HRIS use in the Human Resource Management and Development Department. The activity involved around 25–30 employees as active HRIS users. The methods used included initial observation, technical assistance in using the system, and optimization of HR data management. The results showed that HRIS implementation assistance was able to improve the regularity and completeness of employee data to achieve full validation, reduce recording errors, and accelerate the HR administration process by approximately 50–60% compared to the previous manual method. User acceptance was also relatively high, with around 80% of users stating that HRIS made their work easier. The use of HRIS supports increased work effectiveness, more structured performance monitoring, and data-based decision making within Company X.